Green-urban balance - Ljungman, Henrik (2014)
Rapid urbanization causes competition over land use between green area preservation and urban development in cities and greatly affects ecosystems as well as human well-being. This conflict is significant all around the world as many cities are now replacing existing green areas with new developments. The area around Dag Hammarskjöld's väg in Uppsala is currently experiencing the same conflict, as the need that the city has for new housing represents a threat for the many valuable green areas that are in the site. The purpose of this project was to understand how the need of urban development and the preservation of green areas could be balanced. This understanding would thereafter be used to make a design proposal for the area around Dag Hammarskjöld's väg. First a literature study that focused on three urban design ideologies was made. The three urban design ideologies: The Compact city, the Garden city and Landscape urbanism, were best believed to provide answers for the problem of balancing green area preservation and urban development, and were therefore used to extract ideas as a foundation for six design strategies to help achieve this balance. The design strategies were used to produce a design proposal for the area around Dag Hammarskjöld's väg. The design proposal deals mainly with one issue: the balance between green area preservation and urban development and does not provide a holistic planning solution. The two main results are the design strategies for balancing green area preservation and urban development and the design proposal for the area around Dag Hammarskjöld's väg. The design strategies could be of future use in other projects dealing with similar issues. The design proposal can serve as an example of how to solve this issue in a real site. Furthermore, it could be used by the municipality to inform the future planning of the area.